Environmentally optimized foundation of a railway bridge - Katzenbach, Rolf; Scholz, Markus; Leppla, Steffen; Norkus, Arnoldas (International Conference “Environmental Engineering”, 2023)
The production of materials, e.g., reinforced concrete, and the construction of structures consume large amounts of energy, which lead to a large emission of CO2. Regarding the resulting impact of construction processes on the environment, the reduction of CO2 has an important role. The target is the reduction of the amount of the construction material used and of the energy consumed for construction. For this, the structures have to be optimized regarding the geometry considering the requirements on the stability, the serviceability, and the durability. Bridges are significant rather expensive and complex infrastructural structural units of roads and railways. Foundations for bridges in many cases designed in complicated soil profiles and should resist long-term permanent and variable loadings. General aim in rational foundation design for bridge structures is in maximum evaluation of total bearing capacity of foundation structure, distributing bridge loadings to soil mass in most rational way, id. est. both in shallow and deep layers. The hybrid foundation system Combined Pile-Raft Foundation (CPRF) is a high-tech solution for the transfer of big loads even in settlement active soil. The CPRF combines the bearing capacities of the raft and of the piles. For the design of a CPRF three-dimensional, non-linear calculations using the Finite-Element-Method (FEM) are used. In the first part of the contribution the load-bearing behaviour of a CPRF and the design principles are explained. In the second part, the application in engineering practice is shown by a real case study of a railway bridge with a width of about 110 m. To demonstrate the optimization process, alternative foundation systems were calculated. At the end of the contribution, all foundations systems are compared and evaluated by the savings of CO2 emission.